Bacterial extracellular vesicles and their novel therapeutic applications in health and cancer - Hosseini-Giv, Niloufar; Basas, Alyza; Hicks, Chloe; El-Omar, Emad; El-Assaad, Fatima; Hosseini-Beheshti, Elham (Frontiers in Cellular and Infection Microbiology, 2022)
Bacterial cells communicate with host cells and other bacteria through the release of membrane vesicles known as bacterial extracellular vesicles (BEV). BEV are established mediators of intracellular signaling, stress tolerance, horizontal gene transfer, immune stimulation and pathogenicity. Both Gram-positive and Gram-negative bacteria produce extracellular vesicles through different mechanisms based on cell structure. BEV contain and transfer different types of cargo such as nucleic acids, proteins and lipids, which are used to interact with and affect host cells such as cytotoxicity and immunomodulation. The role of these membranous microvesicles in host communication, intra- and inter-species cell interaction and signaling, and contribution to various diseases have been well demonstrated. Due to their structure, these vesicles can be easily engineered to be utilized for clinical application, as shown with its role in vaccine therapy, and could be used as a diagnostic and cancer drug delivery tool in the future. However, like other novel therapeutic approaches, further investigation and standardization is imperative for BEV to become a routine vector or a conventional treatment method.